Administrative Capacity in Executive Service Delivery: A Literature Review on Government Protocol Functions - Firhan Mahdavikia; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
Administrative capacity has long been recognized as a fundamental determinant of governmental effectiveness, yet its role in executive service delivery, particularly in relation to government protocol functions, remains conceptually underdeveloped in public administration scholarship. Existing studies on administrative capacity predominantly focus on policy formulation, implementation, and citizen-facing service delivery, while research on executive governance and executive support systems often treats internal support functions in aggregate terms. As a result, the specific contribution of protocol functions—as administrative, symbolic, and coordinative mechanisms that sustain executive leadership—has been largely overlooked. Addressing this gap, this literature review examines how administrative capacity operates within executive service delivery, with a particular emphasis on government protocol functions as an integral component of executive support and governance coordination. The primary objective of this article is to synthesize and integrate dispersed theoretical and empirical insights to reconceptualize protocol functions within the broader framework of Administrative Capacity Theory. Employing a narrative–integrative literature review approach, the study systematically selected and analyzed peer-reviewed journal articles from major academic databases published within the last five years. The literature was examined through thematic analysis and conceptual synthesis, guided by Administrative Capacity Theory as the core framework and complemented by perspectives on executive service delivery, institutional capacity, street-level bureaucracy, public service professionalism, and governance coordination. The review identifies recurring patterns indicating that effective executive service delivery depends on the interaction of individual-level capacities (professional competence, discretion, and ethics), organizational-level capacities (structures, procedures, and coordination routines), and system-level capacities (institutional arrangements and governance mechanisms).